KREDIBILITAS, DAYA TARIK, DAN KEWENANGAN PIMPINAN SEBAGAI KOMUNIKATOR TERHADAP ETOS KERJA KARYAWAN - Rusmadi Awza (Universitas Riau, 2012)
Credibility, Attractiveness, and the Authority Leaders As Communicators of EmployeeEthos. The successful tourism development is marked by the number of tourists coming from abroad as,well as domestic to one tourist location. There are many factors which contribute to the success of thistourism sector, among others are the maximum service from the tourism business agencies. The maximumservice which is given to the tourists consists of hotel/inn service and with all of the matters that areinvolved in it. Therefore the role of the leader in motivating his employee is very decisive to the quality ofservice given by the employee. The objective of this research is to examine the influence of credibility,attraction, and the leader authority to the work ethos of hotel employee.